Les ateliers médiévaux de poterie grise en Uzège et dans le Bas-Rhône Premières recherches de terrain - Thiriot, Jacques (Documents d'archéologie française, 1986)
In this publication, Jacques Thiriot, a research worker with the CNRS, presents the results of the fieldwork carried out between 1972 and 1979 on the mediaeval grey pottery workshops of the Uzege and the Lower Rhone, in particular at Saint-Victor-des-Oules in the Gard (XIIth and XIIIth cent.) and Bollene in the Vaucluse (XIIIth cent.). During this work, a methodology adapted to the excavation and interpretation of the remains (ovens and buildings) was perfected, thanks to a rigorous technical analysis. It provided an exceptional insight into production methods in one of the largest mediaeval potter's workshops in south-east France. It has also completed typological data based on pottery found during excavations in user centres, not only in Provence but also in Languedoc. Apart from the subject, rarely dealt with for the mediaeval period, the originality of the work lies in the systematic use of geophysical prospection and scientific methods of dating and in the application of an ethno-archaeological approach which gives a better understanding of mediaeval pottery activities in the region.